8.7 Continuous EEG derived carbon dioxide monitor for newborn preterm babies – levels of agreement with partial pressure of arterial blood carbon dioxide. (9th June 2014) - Jennings, C; McKeering, C; Buriro, A; Gaydeki, P; Victor, S
Abstract : Background: Continuous monitoring of partial pressure of arterial blood carbon dioxide (Pa CO2 ) is important in preterm babies during the first 36 h after birth to avoid episodes of hypo/hypercarbia. There is a need to develop a reliable technique for the continuous monitoring of Pa CO2 . The purpose of this study was to determine if continuous monitoring of Pa CO2 can be performed through the automatic analysis of preterm electroencephalography (EEG). Aim: We aimed to determine the levels of agreement between Pa CO2 measured by blood gas analysis and the partial pressure of carbon dioxide (Peeg CO2 ) predicted by automatic analysis of EEG. Methods: Thirty-six hour EEG recordings using 7 hydrogel leads were performed in 12 babies born before 30 weeks' gestation from soon after birth. Babies with abnormal cranial ultrasound scans were excluded from analysis. Routine arterial blood gases were performed using ABL 835 Flex (Radiometer). EEG was automatically analysed in real-time for changes in amplitude, frequency and interburst intervals in the EEG waveforms. Peeg CO2 was continuously predicted using an algorithm. Impedance was measured hourly and accepted if below 5 kOhms. Artefactual EEG was managed automatically by the software and through qualitative reporting. Results: A strong correlation (R 2 = 0.71; n = 49; p < 0.001) between Pa CO2 and Peeg CO2 was demonstrated. The overall bias (mean difference: Pa CO2 –Peeg CO2 ) was 0.05 kPa and the precision (standard deviation of differences) was 0.56 kPa. Conclusion: Peeg CO2 monitoring is a new development in the field of continuous monitoring in neonatal intensive care. Bias and precision data indicate that it can be a valuable clinical tool.